Permodelan Bangkitan Pada Tata Guna Lahan Sekolah Menengah Atas Swasta di Palembang - yeldy septomiko (Jurnal Teknik Sipil dan Lingkungan, 2014)
The increasing of vehicle amount in urban area, especially in Palembang City causes traffic congestion in many streets at busy hour. This which happens in senior high school at open and close hour can be prevented if before deciding school location, the owner predicts trip generation in the land use. Based on trip generation analyzing of school land use, especially in senior high school, traffic management can be done to solve traffic congestion which will happen.Transport modeling is one method which is used to describe the relation between land use and transportation network by four steps modeling system. They are Trip Generation model, Trip Distribution model, Model split and Trip Assignment. In mathematic double linear regression which is used describes free (Y) and bond variable (X), with constant (a), and regression coefficient (b1,b2,...bn). The formulation of double regression is Y = a + b1 X1 + b2 X2 …….. + bn Xn. Free variable includes student amount (XI), teacher amount (X2), school wide (X3), class amount (X4), class capacity (X5), class wide (X6), facility amount (X7), teacher’s vehicle amount (X8), park area wide (X9). And bond variable includes taker vehicle amount (Y) and picker vehicle amount (Y).The best model to predict trip production for picker vehicles (private and public transport) are Y = = -239,699 + 0,089X1 + 11,200X4 + 10,829X5 with R2 = 0,931. Private car, Y = -287,673 + 0,121X1 + 4,226X4 + 10,294X5 with R2 = 0,864. Motorcycle, Y = 172,967 - 8,269X2 + 0,170X7 + 8,812X9 with R2 = 0,961. Public transport, Y = -382,344 - 0,356X1 + 13,574X4 + 10,269X5 with R2 = 0,905. Key Words : Trip Generation ,Trip Production , Trip Attraction